The Effect of Entrepreneurial Motivation, Family Environment, and Self-Efficacy on Entrepreneurial Intentions - Maisarah Elvia; Corry Yohana; Sefrimel Angriani Zn (The Future of Education Journal, 2026)
Interest in entrepreneurship is one of the key factors in fostering the emergence of new entrepreneurs amid high unemployment rates, particularly among the younger generation. This study aims to analyze the influence of entrepreneurial motivation, family environment, and self-efficacy on interest in entrepreneurship. This study is based on the Theory of Planned Behavior, supported by literature reviews on entrepreneurial motivation, family environment, self-efficacy, and interest in entrepreneurship. The study employs a quantitative approach using a survey method. Primary data were collected through the distribution of a 1–6 Likert-scale questionnaire to 142 Gen Z respondents selected using purposive sampling. Data analysis was conducted using SPSS version 31 software through validity tests, reliability tests, descriptive analysis, classical assumption tests, multiple linear regression analysis, partial t-tests, and the coefficient of determination (R²). The results indicate that entrepreneurial motivation, family environment, and self-efficacy each have a positive and significant effect on entrepreneurial interest. This study concludes that enhancing entrepreneurial motivation, family support, and self-efficacy contributes to increasing entrepreneurial interest among Gen Z